2011
DOI: 10.1055/s-0031-1297031
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activities of Transition Metal Derivatives of Ketoconazole and Clotrimazole against a Wild Type Strain of Saccharomyces cerevisiae in Absence or Presence of Human Neutrophils

Abstract: Summary In vitro activities of a series of gold, copper and ruthenium clotrimazole (CTZ, CAS 23593-75-1) and ketoconazole (KTZ, CAS 65277-42-1) derivatives were investigated individually and in combination with human neutrophils (PMNs) against a wild type strain of Saccharomyces cerevisiae. For 11 out of 12 tested metal complexes, the minimal inhibitory concentrations (MICs) at which 100 % of yeast growth was inhibited ranged from 0.75 to 3.0 ?mol/L. The complex RuCl3(CTZ)3 ? 2CH3OH (1f) (MIC = 0.75 ?mol/L) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Because the latter were significantly higher than their corresponding MICs, and because the trypan blue exclusion method showed that none of the compounds was significantly cytotoxic toward Neutrophils below 100 µM, it was determined if a 0.5 µM concentration of the complexes could enhance the activity of the phagocytes. This was, however, not the case for the Ctz coordination compounds [104].…”
Section: Coordination Compounds Of the Ctz Family Of Aasmentioning
confidence: 79%
See 1 more Smart Citation
“…Because the latter were significantly higher than their corresponding MICs, and because the trypan blue exclusion method showed that none of the compounds was significantly cytotoxic toward Neutrophils below 100 µM, it was determined if a 0.5 µM concentration of the complexes could enhance the activity of the phagocytes. This was, however, not the case for the Ctz coordination compounds [104].…”
Section: Coordination Compounds Of the Ctz Family Of Aasmentioning
confidence: 79%
“…Their MIC values lay in the low micromolar range, close to that of the uncoordinated AA at 1 µM. All measured IC 50 values on human neutrophils were several times higher than the corresponding MICs, and even though 91 seemed to significantly improve the defense ability of these white blood cells regarding phagocytosis and killing percentages, such results are hard to put in perspective, due to absence of reference data in the paper [104]. In 2018, the authors continued their antifungal study on these types of Au(I), Cu(I) and Pt(II) complexes bearing AAs, with compounds featuring Ktz ligands.…”
Section: Coordination Compounds Of the Ktz Family Of Aasmentioning
confidence: 86%
“…Some coordination compounds, like zinc(II) complex with the organic ligand 2-(3,4-dichlorophenyl)imino-N-(4H-5,6-dihydro-1,3-thiazin-2-yl)tetrahydro-1,3-thiazine [4] and copper(II) and ruthenium(II) complexes of the antifungal drug Ketoconazole [3] improve phagocytosis with respect to organic ligand. In other cases, metal complexes do not affect neutrophils phagocytosis as occur for one zinc(II) complex [4] and some gold(I), copper(II) and ruthenium(II) complexes [3]. Finally, in the case of certain diclofenac transition metal complexes [5] the phagocytosis decreases with respect to the drug.…”
Section: Study Of the Phagocytic Functionmentioning
confidence: 99%
“…Likewise, coordination compounds interfere with in vitro phagocytosis showing either improve, like copper(II) and ruthenium(II) complexes of the antifungal drug Ketoconazole [3] and one zinc(II) complex with the organic ligand 2- (3,4-dichlorophenyl)imino-N-(4H-5,6-dihydro-1,3-thiazin-2-yl)tetrahydro-1,3-thiazine [4], or decrease, as it is the case of certain diclofenac transition metal complexes [5].…”
Section: Introductionmentioning
confidence: 99%